Widespread Cortical Demyelination in Geriatric Cases of Mild Traumatic Brain Injury and in Alzheimer's Disease. (17th December 2021) - Irimia, Andrei; Chowdhury, Nahian; Wang, Shania; Mahoney, Sean; Van Ngo,; Rostowsky, Kenneth; Hacker, Benjamin; Chaudhari, Nikhil
Abstract: Cortical demyelination is related to neurodegeneration after mild traumatic brain injury (mTBI) and Alzheimer's disease (AD). The ratio R of T1-to-T2-weighted magnetic resonance image (MRI) intensities is proportional to myelin content, and allows myelin changes to be mapped in vivo. T1 and T2 MRIs were acquired from mTBI patients (N = 97, age μ = 41 y; σ = 19 y, range: 21-79) both acutely and chronically ( 1 week and 6 months post-injury, respectively), from AD patients (N = 80, age μ = 76 y; σ = 8 y, range: 55-88), and from cognitively normal (CN) adults (N = 78, age μ = 75 y; σ = 5 y, range: 12-90). AD and CN subjects' data were acquired less than a year apart. MRIs were analyzed using 3DSlicer's BRAINSfit (registration), FreeSurfer (segmentation), SPM12 (bias field correction) and custom MATLAB scripts to calculate myelin content and demyelination. The null hypothesis of no myelin change was tested at each cortical location for each pair of groups (α = 0.05), after accounting for age, sex and interscan interval. Compared to HCs, AD subjects featured significantly greater myelin loss in dorsolateral prefrontal cortex, lateral and medial temporal lobes ( 52% of the cortex, p < 0.05). mTBI participants experienced significantly greater myelin loss across 96% of the cortex (p < 0.05), suggesting that mTBI has dramatic impact upon cortical myelin content. Myelin loss magnitude was comparable across mTBI and AD, particularly within temporal lobes. Future research should study whether post-traumatic demyelination increases the AD risk.